ANALISIS PENGENDALIAN PRODUK CACAT DENGAN METODE FOUR QUALITY CONTROL (4QC) TOOLS - HERY PURNOMO; LILIA PASCA RIANI (AKADEMIKA, 2018)
The purpose of this study is to determine the extent to which the control of defective productsin PT Bisi International Tbk. Kediri, a producer of corn seeds in Kediri Regency. Themethods used are Historam, Pareto Diagram, P-Chat 3 sigma control chart and Cause Effectdiagram at the production stage. The results showed that by using the Histogram graph, itcan be concluded that the number of product defects is mostly in the process of Ear Shortir,pareto diagram shows 69% disability is on the type of seed that is too young and corn seed isless perfect, so with the mitigation of both types of defect, the company can reduce productdefect rate by 69%. On the 3 sigma P Chart, it is known that observations 2 and 7 are abovethe upper control limit, and at 8th observations are below the lower control limits. Analysisof Cause Effect diagram shows there are 6 main sources of causes of product defects, namelyfrom aspects of HR, Equipment, Procedure, Material, and other causes.